The Message and the Text Typological modelThe problematic of classification (مجلة إحالات, 2026)
The studies which are interested in the study of the manner of the constitution of the texts in the 1970shave known a successive progressions, but since the change of the point of view based on the study of thesentence - as a maximum level at which the description can reach- and the investigation of its sytactic and semantic truth, the concern began by treating questions relating to texts as successive sentences containing auniversal issue, and also because the question of classifying the texts is considered as one of those which have preoccupied the researchers in textual linguistics in one of the stages of the development of this science, thisstudy is included within the attempts of the analysis of one of the types of communicative literary texts ( the message) in order to defining the theory of types of the texts and also how to classify the texts in specificmodels.